2013
DOI: 10.1155/2013/105318
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Hybrid Pixel Detectors in the Search for the Neutrinoless Double-Beta Decay of116Cd

Abstract: We investigated the potential of the energy resolving hybrid pixel detector Timepix contacted to a CdTe sensor layer for the search for the neutrinoless double-beta decay ofCd. We found that a CdTe sensor layer with 3 mm thickness and 165 μm pixel pitch is optimal with respect to the effective Majorana neutrino mass (mββ) sensitivity. In simulations, we were able to demonstrate a possible reduction of the background level caused by single electrons by approximately 75% at a specific background rate of 10−3coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 42 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…We already showed that alpha particle background can be reduced by at least a factor of 4.32 • 10 5 with a 0νβ β signal loss of less than 4.5% [9]. Single electron background can be rejected by 75% with a signal loss of about 25% [10]. While a thick sensor increases the detection efficiency, it also has a negative influence on the energy resolution.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We already showed that alpha particle background can be reduced by at least a factor of 4.32 • 10 5 with a 0νβ β signal loss of less than 4.5% [9]. Single electron background can be rejected by 75% with a signal loss of about 25% [10]. While a thick sensor increases the detection efficiency, it also has a negative influence on the energy resolution.…”
Section: Introductionmentioning
confidence: 90%
“…While a thick sensor increases the detection efficiency, it also has a negative influence on the energy resolution. We showed that with the current Timepix, the detectors should optimally have a thickness of about 3 mm [10]. So compared to monolithic coplanar grid detectors a lot more detectors are required to obtain the same nuclide mass, which translates to higher cost, higher energy consumption, more channels to read out and calibrate and more background since the mass to surface ratio is less favourable.…”
Section: Introductionmentioning
confidence: 99%
“…COBRA is also exploring the use of pixelized detectors, which have the potential to further reduce the background using topological information. These efforts are not considered in this paper but are discussed in [5].…”
Section: Cpg Capabilitiesmentioning
confidence: 99%
“…Such applications include space weather analyses [7], the determination of trapped particle directions in the Van-Allen radiation belts [8,9], monitoring of secondary radiation in hadron therapy [10], the study of the antiproton annihilation [4] and electron microscopy [11]. Especially, when equipped with CdTe or CdZnTe as sensor material Timepix detectors can be investigated for double beta decay experiments [12]. All of the above applications would profit significantly from a determination of the interaction depth in the sensor by improving particle discrimination, background event suppression, annihilation vertex reconstruction, impact angle or impact point determination.…”
Section: Introductionmentioning
confidence: 99%